Research on Overflow Monitoring Mechanism Based on Downhole Microflow Detection. (16th December 2014) - Ge, Liang; Hu, Ze; Chen, Ping; Shi, Lei; Yang, Qing; Liao, Junbi
Abstract : The flow rate variation of the drilling fluid and micro-overflow loss is difficult to analyze. The purpose to prevent the occurrence of kick, lost circulation, and other complex conditions is not easy to be achieved. Therefore, the microflow-induced annulus multiphase flow rate and annulus pressure field model were studied, and a downhole microflow measurement system has been developed. A differential pressure type flow measurement was used in the system, and real-time downhole information was obtained to achieve deep, narrow windows and other safety-density complex formation security. This paper introduced a new bottom-hole flow meter which can measure the annular flux while drilling and monitor overflow and circulation loss. The accuracy and reliability of the MPD (managed pressure drilling) system can be improved obviously by applying the device; as a result, the safety of drilling is enhanced and the cost is reduced.